Exposição pessoal de curto prazo ao material particulado fino e a sua composição química elementar - Moreira, Camila Arielle Bufato (2017)
Studies of the personal exposures for particulate matter are scarce and practically non-existent with an assessment of their chemistry. The personal exposure to air pollution occurs in indoor and outdoor, being dependent on the time of stay in these environments, in addition to the proximity of pollution sources and influence of the meteorological conditions. This study aimed to assessment the short-term the concentrations of fine particulate matter and the elemental chemical composition. Thus, measurements and PM2.5 collections were carried out at a rate similar to human respiration (MIE monitor pDR-1500 ™) in a convenience sample with 30 volunteers during a typical work and/or study day, which were georeferenced (GPS DG -100 Data Logger). For better inference about the exposure in the displacements were also performed measurements and PM2.5 collections were also carried out in five bus lines and during periods of greater and lesser flow of users. The samplings were carried out in triplicates, in order to characterize the real exposure of the population during the daily journeys for work and/or study, following the same parameters of the personal sampling. The determination of the Black Carbon equivalent (BCe) concentration in the filters used in the personal sampling was carried out, following the light reflectance method and applied to the ED-XRF technique to analyze the PTFE filters.The mean concentrations of PM2.5 of the volunteers in the car and bus groups were 12.4 μg m-3 and 10.7 μg m-3 respectively. In addition, to BCe, mean concentrations were 4.3 μg m-3 for the group of volunteers who traveled by bus and 4.1 μg m-3 for volunteers who used cars. The bus group indicated the highest average concentrations for the trace elements Na, S and K, whereas the car group were S, Fe, Na and K. In average, the volunteers of the bus group inhaled a dose of 0.027 μg / kg-h of PM2.5, while the automobile group inhaled 0.029 μg/kg-hr. In terms of PM2.5 mass concentration and BCe, the exposure of users is greater in the peak with concentration of the 18.8 μg m-3, 7.8 μg m-³ respectively. In addition, the exposure of users is not similar in the five lines, suggesting the influence of local sources on bus routes (industrial, biomass burning and waste).The trace elements that presented the highest concentrations for the non-peak and peak hours were those derived from vehicle emissions, such as S, K and Na, which were associated, specifically Na, to the presence of biodiesel in diesel. Following are the elements from soil dust suspension such as Al, Si, Ca, Mg and Fe. The mean inhaled dose of PM2.5 for the peak was 0.05 μg / kg-hour and for the non-peak 0.04 μg / kg-hour. In this study, the main source of emission is the vehicle traffic, for sampling was performed directly inside the buses, in urban routes, as well as for the volunteers who were generally in the displacements or work exposed to emissions of vehicular origin, resuspension of dust, emissions related to the wear of the vehicles. Therefore, it can be concluded that in the urban environment the emissions of vehicular origin are predominant and that the urban morphology can contribute to the accumulation of pollutants increasing the dose received by the population.